Flow-Induced Axial Vascularization: The Arteriovenous Loop in Angiogenesis and Tissue Engineering - Leibig, Nico; Wietbrock, Johanna O.; Bigdeli, Amir Khosrow; Horch, Raymund E.; Kremer, Thomas; Kneser, Ulrich; Schmidt, Volker-Jürgen (Plastic and reconstructive surgery, 2016)
Summary: - Fabrication of a viable vascular network providing oxygen supply is identified as one crucial limiting factor to generate more complex three-dimensional constructs. The arteriovenous loop model provides initial blood supply and has a high angioinductive potency, making it suitable for vascularization of larger, tissue-engineered constructs. Also because of its angiogenic capabilities the arteriovenous loop is recently also used as a model to evaluate angiogenesis in vivo. This review summarizes the history of the arteriovenous loop model in research and its technical and surgical aspects. Through modifications of the isolation chamber and its containing matrices, tissue generation can be enhanced. In addition, matrices can be used as release systems for local application of growth factors, such as vascular endothelial growth factor and basic fibroblast growth factor, to affect vascular network formation. A special focus in this review is set on the assessment of angiogenesis in the arteriovenous loop model. This model provides good conditions for assessment of angiogenesis with the initial cell-free environment of the isolation chamber, which is vascularized by the arteriovenous loop. Because of the angiogenic capabilities of the arteriovenous loop model, different attempts were performed to create functional tissue in the isolation chamber for potential clinical application. Arteriovenous loops in combination with autologous bone marrow aspirate were already used to reconstruct large bone defects in humans.
Gesehen am 18.06.2020